Daratumumab-associated varicella-zoster virus meningoencephalitis in relapsed refractory multiple myeloma - Turgutkaya, Atakan; Bolaman, Ali Zahit; Yavaşoğlu, İrfan (Acta Medica, 2024)
Daratumumab is a widely-used monoclonal anti-CD38 antibody both in newly-diagnosed and relapsed refractory multiple myeloma. CD38 is expressed on the surface of NK, regulatory B, and T cells. Therefore, patients receiving the drug are prone to decreased immunity, especially against herpes virus infections. Varicella-zoster virus is one of the herpesviruses, and reinfection typically occurs in immunocompromised individuals, including multiple myeloma patients, by reactivation of endogenous latent infection within the sensory ganglia. This type of infection (herpes zoster) usually presents in a dermatomal skin area. Here, we report a patient who developed varicella-zoster virus meningoencephalitis under daratumumab treatment.